2020
DOI: 10.29333/ejgm/8460
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Latin America: A Bibliometric Analysis of Scientific Publications in Health

Abstract: The coronavirus disease (COVID-19) has become a global health crisis. The scientific community has responded with a sizable level of research and publications, many of which are beginning to be identified and analyzed in systematic reviews of the literature and bibliometric studies. No readily identifiable, comparable study focused on Latin American scientific literature has been undertaken thus far. Therefore, this article analyzes such literature, focused on COVID-19, and one that has been published in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
20
0
3
Order By: Relevance
“…Similarly, some bibliometrics-based studies focus on the publications in some specific time periods, such as the first eight months in 2020 (Furstenau et al, 2021), the early stage of the outbreak (Gong Y. et al, 2020;Zyoud & Al-Jabi, 2020), etc. There are also some bibliometrics analyses that focus on some specific countries or regions (Gallegos et al, 2020;Raju & Patil, 2020) or publication sources (Oh & Kim, 2020). Beyond that, most of the bibliometrics analyses focus on some specific topics or fields, including COVID-19 and environment (Casado-Aranda et al, 2021;, mental health and COVID-19 (Maalouf et al, 2021), COVID-19 and machine learning (Chiroma et al, 2020;De Felice & Polimeni, 2020), COVID-19 and business and management (Rodrigues et al, 2020;Verma & Gustafsson, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some bibliometrics-based studies focus on the publications in some specific time periods, such as the first eight months in 2020 (Furstenau et al, 2021), the early stage of the outbreak (Gong Y. et al, 2020;Zyoud & Al-Jabi, 2020), etc. There are also some bibliometrics analyses that focus on some specific countries or regions (Gallegos et al, 2020;Raju & Patil, 2020) or publication sources (Oh & Kim, 2020). Beyond that, most of the bibliometrics analyses focus on some specific topics or fields, including COVID-19 and environment (Casado-Aranda et al, 2021;, mental health and COVID-19 (Maalouf et al, 2021), COVID-19 and machine learning (Chiroma et al, 2020;De Felice & Polimeni, 2020), COVID-19 and business and management (Rodrigues et al, 2020;Verma & Gustafsson, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, LAC researchers preferred to publish in Travel Medicine Infectious Disease journal as described elsewhere [16]. However, another bibliometric analysis found that Cadernos de Saúde Pública was the most prevalent journal [22], which is not surprising, considering that Brazil is the main producer of the region.…”
Section: Discussionmentioning
confidence: 99%
“…Like in review articles [23][24][25], the utilization of Bibliometrics Analysis, a tool and technique widely used by many researchers worldwide [26,27], presents a cumulative understanding of malnutrition eradication effort. The analytical approach of annual trends of publication, institutions, journals, authors, country and international collaboration networks, citations, keywords occurrence, and contributed funding agency can help researchers and decisionmakers gain insight into the research productivity to understand scientific research progress in malnutrition-related publications better.…”
Section: Introductionmentioning
confidence: 99%